ผลของชนิดและอัตราปุ๋ยเคมีต่อการเจริญเติบโตของไผ่ตงหม้อ - พวงจิก ธัญพิสิษฐ์; ฤทธิ์เพชร ต้องใจ; หาระโคตร พรชัย (Thai Journal of Science and Technology, 2019)
Abstract This experiment studied the effects of the chemical fertilizer formulas and rates on growth of Dendrocalamus asper Backer bamboo. The trial was arranged in a Completely Randomized Design (CRD) with three replications. Seven treatments included no chemical fertilizer application (control), 46-0-0 fertilizer at 15 and 20 gram/pot/time rates, 16-16-16 fertilizer at 15 and 20 gram/pot/time rates, and 46-0-0 mixed with 16-16-16 fertilizers at 15 and 20 gram/pot/time rates. The bamboo growth data were collected after 3, 6 and 9 months of cultivation. The results showed that the 46-0-0 fertilizer at 15 gram/pot/time rate resulted in the highest nitrogen content in bamboo leaves as well as potassium content in bamboo stems (1.25 and 1.28 %, respectively). A 16-16-16 fertilizer at 20 gram/pot/time rate promoted the new shoots after 3 and 9 months of cultivation (8 and 7.7 shoots/pot, respectively). Moreover, this fertilizer formula and rate also resulted in the highest stem at 3 and 6 months after cultivation (155.14 and 312.39 cm, respectively). The 46-0-0 with 16-16-16 fertilizer at 15 gram/pot/time rate gave the highest bamboo height at 9 months after transplanting (357.33 cm). These chemical fertilizer formula at 20 gram/pot/time rate resulted in the highest nitrogen content in bamboo stems (0.73 %). However, chemical fertilizer application caused the significantly decreased pH of the growing media. Keywords: Dendrocalamus asper; chemical fertilizer; growth